Schema-based instruction: Effects of experienced and novice teacher implementers on seventh grade students' proportional problem solving. (August 2016) - Jitendra, Asha K.; Harwell, Michael R.; Karl, Stacy R.; Dupuis, Danielle N.; Simonson, Gregory R.; Slater, Susan C.; Lein, Amy E.
Abstract: This study examined the effects of a research-based intervention, schema-based instruction (SBI), implemented by experienced- (taught SBI in previous study;Jitendra et al., 2015 ) and novice-teacher implementers (taught SBI for the first time with professional development) on the mathematics outcomes of seventh-grade students. SBI is a multicomponent intervention that emphasizes the mathematical structure of problems through the use of schematic diagrams and incorporates problem solving and metacognitive strategy instruction. Results indicated that both experienced- and novice-teacher implementers delivered SBI with similar levels of fidelity; there was no SBI experience effect on the immediate and 10-week retention tests of proportional problem-solving, on a general measure of problem solving, or on the end of the year state mathematics achievement test. These results provide evidence that the effectiveness of SBI generalizes over time to different cohorts of teachers and that the impact of SBI on student mathematics outcomes is maintained over time without additional PD. Highlights: Assessed effects of PD and SBI with experienced- and novice-teacher implementers. Both cohorts of teachers implemented SBI with similar levels of fidelity. The effectiveness of SBI generalized over time to different cohorts of teachers. Student learning in classrooms of both cohorts is maintained over time. Findings suggest that well-designed instructional materials can influence learning.